2011
DOI: 10.1007/s11242-011-9794-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cross Correlations Between Well Logs of Hydrocarbon Reservoirs

Abstract: We carry out a series of cross-correlation analysis of raw well-log data, in order to study the possible connection between natural gamma ray (GR) logs and other types of well logs, such as neutron porosity (NPHI), sonic transient time (denoted usually by DT), and bulk density (RHOB) of oil and gas reservoirs. Three distinct, but complementary, methods are used to analyze the cross correlations, namely, the multifractal detrended cross-correlation analysis (MF-DXA), the so-called Q cc (m) test in conjunction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Indeed, small discrepancies are acceptable in statistical treatments. This last result is in agreement with Dashtian et al (2011a), who used cross-correlation analysis between well logs and found that sonic, porosity and density are more correlated between them than gamma ray.…”
Section: Final Remarkssupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, small discrepancies are acceptable in statistical treatments. This last result is in agreement with Dashtian et al (2011a), who used cross-correlation analysis between well logs and found that sonic, porosity and density are more correlated between them than gamma ray.…”
Section: Final Remarkssupporting
confidence: 91%
“…In references Andrade et al (2009), Chun-Feng and, Gholamy et al (2008) and Tavares et al (2005), DFA is employed to interpret and filter images of seismograms. In references Ribeiro et al (2011), Lozada-Zumeta et al (2012, and Dashtian et al (2011a), this technique is used, as in this manuscript, in the analysis of well logs.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…As more information regarding the reservoir properties is collected, the uncertainty associated with the recovery of hydrocarbons decreased. Reservoir characteristics have long been studied by means of a variety of techniques such as well log data (Dashtian et al 2011), well test data (Braester and Zeitoun 1993;Vaferi et al 2011), seismic data (Arora and Tomar 2010), and well drilling data (Weber 1993). Among these methods, recording transient well pressures created by flow rate alteration is a useful measure to obtain reservoir properties (Athichanagorn and Horne 1995;Gringarten 1987;Sanni and Gringarten 2008;Vaferi and Eslamloueyan 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the neural network based correlation techniques, the neurons are initially trained to identify a particular geologic marker for a given well and subsequently these are used to identify the markers in other wells. In the cross-correlation based well correlation techniques, the cross-correlation of raw well log data for corresponding logs between wells are done and a high correlation implies a correlation of strata (Dashtian et al 2011). The artificial intelligence based techniques suffer from the drawback that it is not able to identify gaps and stretching of sequences which probably might be due to the presence of uncorrelated strata.…”
Section: Introductionmentioning
confidence: 99%